The factors associated with distress following exposure to smoke from an extended coal mine fire. (November 2020) - Broder, Jonathan C.; Gao, Caroline X.; Campbell, Timothy C.H.; Berger, Emily; Maybery, Darryl; McFarlane, Alexander; Tsoutsoulis, Jessica; Ikin, Jillian; Abramson, Michael J.; Sim, Malcolm R.; Walker, Judi; Luhar, Ashok; et al.
Abstract: In February 2014, the coalmine adjacent to the Hazelwood Power Station in the Latrobe Valley of Victoria, Australia, caught fire, with residents from the nearby town of Morwell and the wider area exposed to smoke for six weeks. Although there was evidence linking the mine-fire event with psychological distress, no studies have evaluated the degree of distress in relation to the level of smoke exposure. We aimed to investigate the exposure-response relationship between particulate matter 2.5 μm or less in diameter (PM2.5 ) released during the Hazelwood mine fire event and long-term symptoms of posttraumatic distress in the affected community, including the consideration of other key factors. A total of 3096 Morwell residents, and 960 residents from the largely unexposed comparison community of Sale, were assessed for symptoms of posttraumatic distress 2.5 years after the Hazelwood incident using the Impact of Events Scale-Revised (IES-R). Individual-level PM2.5 exposure was estimated by mapping participants' self-reported location data on modelled PM2.5 concentrations related to the mine fire. Multivariate linear regression was used to evaluate the exposure-response relationship. Both mean and peak exposure to mine fire-related PM2.5 were found to be associated with participant IES-R scores with an interaction effect between age and mean PM2.5 exposure also identified. Each 10 μg/m 3 increase in mean PM2.5 exposure corresponded to a 0.98 increase in IES-R score (95% CI: 0.36 to 1.61), and each 100 μg/m 3 increase in peak PM2.5 exposure corresponded to a 0.36 increase (95% CI: 0.06 to 0.67). An age-effect was observed, with the exposure-response association found to be stronger for younger adults. The results suggest that increased exposure to PM2.5 emissions from the Hazelwood mine fire event was associated with higher levels of psychological distress associated with the mine fire and the most pronounced effect was on younger adults living in the affected community. Graphical abstract: Image 1 Highlights: PM2.5 exposure was objectively estimated at an individual level. An exposure-response relationship was observed between PM2.5 and distress. Younger adults reported higher distress in response to increased exposure. Other factors such as prior traumatic experiences were related to distress. This work provides a nuanced understanding of distress following a pollution event.